Association of the Presenting Glasgow Coma Scale in patients who requires ICU admission or operative intervention following traumatic brain injury with the Marshall computed tomography (CT) classification of traumatic brain injury - Joshi, Sumit; Paudel, Prakash; Shah, Damber Bikram; Karki, Prasanna; Sharma, Gopal R. (Nepal Mediciti Medical Journal, 2022)
BACKGROUND Glasgow coma scale (GCS) and Marshall computed tomography classification of traumatic brain injury can predict the severity of the brain injury in patients following trauma. This study aims to analyse the association between two, in patients who required ICU admission or neurosurgical intervention following trauma. METHODOLOGY Retrospective study of 64 patients who underwent ICU admission or neurosurgical intervention following traumatic brain injury from September 2017 to December 2020 in Nepal Mediciti Hospital. Majority of the mild head injury where CT scan was not performed, discharged from the emergency or did not need ICU admission or admitted in ward for observation, severe polytrauma were excluded from the study. Glasgow coma Scale was categorized into mild (13-15), moderate (9-12) and severe (<8). The Marshall CT scan Grade was dichotomized into (1-3) and (4-6). RESULTS Out 64 patients, majority were male 48 (84.4%), mean age 42.33 (SD±16.16). In admitted patients, 48.4 %( GCS< 8), 39.1% (GCS 9-12), 12.5% (GCS 13-15).The higher marshal grade (4-6) was present in 93.54 %( <8), 48% (9-12), 25% (13-15). There was significant association of the GCS with the Marshall CT scan grade (p=0.00). CONCLUSION There is significant association between the presenting GCS and Marshall CT Scan grade following TBI. The more severe patients with decreasing GCS have higher Marshall CT Scan grade in CT scan of the brain.